Islamic banking - Iqbal, Zubair; Mirakhor, abbas; International Monetary Fund (IMF) (Washington D.C: International Monetary fund, 1987)
The author of this book based his research findings on two Islamic countries i. e. Iran and Pakistan, the paper further describes the certainty and salient features of an Islamic banking system and analysis and it experiences.
bibliography 60-62
asm; 15/02/19
Loans
Keywords: Islamic countries; Bank and banking; Iran and Pakistan